The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Realising the potential of interoperable data products to improve the outlook for marine biodiversity: Lessons from the European marine observation and data network - Thomas J. Webb; Joana Beja; Salvador Jesús Fernández Bejarano; Elvira Ramos; Samuel Sainz-Villegas; Karline Soetaert; Willem Stolte; Charles Troupin; Benjamin Weigel (Marine Policy, 2025)

Diverging benthic trait diversity and drivers across fjord to slope habitats of the high Arctic - Phoebe Armitage; Anna Törnroos; Rosalyn Fredriksen; Bodil A. Bluhm; Benjamin Weigel; Erik Bonsdorff; Jørgen S. Christiansen; Marie C. Nordström (Estuarine, Coastal and Shelf Science, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Comprehensive analysis of 19 cannabinoids in commercial CBD oils: concentrations, profiles, and safety implications - Niklas Lindekamp; Stefan Weigel; Benjamin Sachse; Bernd Schäfer; Sascha Rohn; Nadja Triesch (Journal of Consumer Protection and Food Safety, 2024)
Nineteen cannabinoids, including Δ 9 -THC (tetrahydrocannabinol) and CBD (cannabidiol), were quantified in 22 CBD oils, 2 CBG (cannabigerol) oils, and 2 CBN (cannabinol) oils, marketed as food supplements, aroma oils, or cosmetic preparations. Analyses were conducted using high-performance liquid chromatography coupled to tandem mass spectrometry (HPLC-MS/MS). The declared concentrations of CBD (or CBG, CBN) in the oils ranged from 2.5 to 20%. Actual concentrations compared to declared concentrations ranged from 81 to 226%. CBD concentrations of up to 9 mg per drop were found. Δ 9 -THC was detected in 20 of 26 samples, with concentrations ranging from 5 to 1576 mg/kg (mean = 536 mg/kg). Considering the highest daily intake suggested by one manufacturer (20 drops) and a body weight of 70 kg, the measured Δ 9 -THC concentration in 50% (n = 13) of the products would exceed the acute reference dose (ARfD) of 1 µg/kg body weight (bw) derived for Δ 9 -THC by the European Food Safety Authority (EFSA). For 7 samples, only 2 drops of oil would be sufficient to exceed the ARfD of Δ 9 -THC.

Strategies for integrating scientific evidence in water policy and law in the face of uncertainty - Niina Kotamäki; George Arhonditsis; Turo Hjerppe; Kari Hyytiäinen; Olli Malve; Otso Ovaskainen; Tiina Paloniitty; Jukka Similä; Niko Soininen; Benjamin Weigel; Anna-Stiina Heiskanen (Science of The Total Environment, 2024)

Macrosystem community change in lake phytoplankton and its implications for diversity and function - Benjamin Weigel; Niina Kotamäki; Olli Malve; Kristiina Vuorio; Otso Ovaskainen (Global Ecology and Biogeography, 2023)
Aim We use lake phytoplankton community data to quantify the spatio‐temporal and scale‐dependent impacts of eutrophication, land‐use and climate change on species niches and community assembly processes while accounting for species traits and phylogenetic constraints. Location Finland. Time period 1977–2017. Major taxa Phytoplankton. Methods We use hierarchical modelling of species communities (HMSC) to model metacommunity trajectories at 853 lakes over four decades of environmental change, including a hierarchical spatial structure to account for scale‐dependent processes. Using a “region of common profile” approach, we evaluate compositional changes of species communities and trait profiles and investigate their temporal development. Results We demonstrate the emergence of novel and widespread community composition clusters in previously more compositionally homogeneous communities, with cluster‐specific community trait profiles, indicating functional differences. A strong phylogenetic signal of species responses to the environment implies similar responses among closely related taxa. Community cluster‐specific species prevalence indicates lower taxonomic dispersion within the current dominant clusters compared with the historically dominant cluster and an overall higher prevalence of smaller species sizes within communities. Our findings denote profound spatio‐temporal structuring of species co‐occurrence patterns and highlight functional differences of lake phytoplankton communities. Main conclusions Diverging community trajectories have led to a nationwide reshuffling of lake phytoplankton communities. At regional and national scales, lakes are not single entities but metacommunity hubs in an interconnected waterscape. The assembly mechanisms of phytoplankton communities are strongly structured by spatio‐temporal dynamics, which have led to novel community types, but only a minor part of this reshuffling could be linked to temporal environmental change.

Responses of coastal fishery resources to rapid environmental changes - Heikki Peltonen; Benjamin Weigel (Journal of Fish Biology, 2022)
Coastal systems experience strong impacts of ongoing environmental change, affecting fish communities and subsequently fishery yields. In the Baltic Sea, the combined effects of climate‐induced changes and eutrophication‐related pressures constitute major threats to its living resources. Although much work has been devoted to uncovering environmental impacts on the commercially most valuable fish stocks, only little is known about community‐wide responses of fished species and how environmental change may affect their yield. In this study, the authors use a joint species distribution modelling framework to disentangle environmental impacts on species‐specific fishery yields of 16 fished species along the coast of Finland over four decades. The authors show that environmental covariates substantially contributed to variations in fishery yields and are likely to have strong impacts on fished resources also in the future. Salinity and near‐bottom oxygen concentration emerged as the strongest environmental drivers of yields at the community level, whereas temperature was particularly important for cod ( Gadus morhua ) and sprat ( Sprattus sprattus ) yields. The authors found shore density to be an important predictor for fisheries resources especially for freshwater fish. The results of this study suggest that the changes in environmental conditions during the past four decades had a positive effect on the yields of freshwater and warm‐affinity species, whereas yields of marine cold‐affinity species have been mainly negatively affected by contracting favourable habitats, becoming warmer and less saline.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Cerebral resting state markers of biased perception in social anxiety - Benjamin Kreifelts; Lena Weigel; Thomas Ethofer; Carolin Brück; Michael Erb; Dirk Wildgruber (Brain Structure and Function, 2019)

The importance of benthic–pelagic coupling for marine ecosystem functioning in a changing world - Jennifer R. Griffiths; Martina Kadin; Francisco J. A. Nascimento; Tobias Tamelander; Anna Törnroos; Stefano Bonaglia; Erik Bonsdorff; Volker Brüchert; Anna Gårdmark; Marie Järnström; Jonne Kotta; Martin Lindegren; et al. (Global Change Biology, 2017)
Benthic–pelagic coupling is manifested as the exchange of energy, mass, or nutrients between benthic and pelagic habitats. It plays a prominent role in aquatic ecosystems, and it is crucial to functions from nutrient cycling to energy transfer in food webs. Coastal and estuarine ecosystem structure and function are strongly affected by anthropogenic pressures; however, there are large gaps in our understanding of the responses of inorganic nutrient and organic matter fluxes between benthic habitats and the water column. We illustrate the varied nature of physical and biological benthic–pelagic coupling processes and their potential sensitivity to three anthropogenic pressures – climate change, nutrient loading, and fishing – using the Baltic Sea as a case study and summarize current knowledge on the exchange of inorganic nutrients and organic material between habitats. Traditionally measured benthic–pelagic coupling processes (e.g., nutrient exchange and sedimentation of organic material) are to some extent quantifiable, but the magnitude and variability of biological processes are rarely assessed, preventing quantitative comparisons. Changing oxygen conditions will continue to have widespread effects on the processes that govern inorganic and organic matter exchange among habitats while climate change and nutrient load reductions may have large effects on organic matter sedimentation. Many biological processes (predation, bioturbation) are expected to be sensitive to anthropogenic drivers, but the outcomes for ecosystem function are largely unknown. We emphasize how improved empirical and experimental understanding of benthic–pelagic coupling processes and their variability are necessary to inform models that can quantify the feedbacks among processes and ecosystem responses to a changing world.

Impact of eutrophication and climate change on fish and zoobenthos in coastal waters of the Baltic Sea - Martin Snickars; Benjamin Weigel; Erik Bonsdorff (Marine Biology, 2015)